Eating Disorders: Assessment of Knowledge on a Dentist’s Sample - Lumbau, Aurea; Spano, Giovanni; Meloni, Silvio Mario; Sanna, Francesca; Lugliè, Pietrina Francesca (International Journal of Child Health and Nutrition, 2015)
Aim: To analyze the knowledge and experience of dentists with private practices in the Sassari district with regard to eating disorders and clinical stomatology manifestations. Methods: A questionnaire to investigate dentists’ knowledge and experience was created and submitted to a random sample of dentists. Data were collected and analysed using the Stata SE 10 software. Results: In total, 150 dentists were enrolled (a representative sample). After questionnaire evaluation, the following results were obtained: 80.7% (121) of the participants had a degree in dentistry and 19.3% (29) had degrees in medicine with a dentistry master of science diploma, 46% (69) were males and 54% (81) were females, their age range was 25-62 (mean, 36.1) years, and the average work experience was 11.5 (range, 1-36) years. More than 90% of the participants defined eating disorders only as bulimia and anorexia. Of the dentists, 77.3% (116) correctly identified Western populations as the most affected, whereas 52.7% identified only whites as the most affected people. In total, 80% of the dentists recognised dental erosion and abrasion as typical oral manifestations. Only 62% stated that salivary pH decreases in these conditions, and 63% did not recognise parotid gland tumefaction as a clinical sign. Regarding operator experience, 60.7% (91 dentists) had clinical experience of patients with eating disorders: 43.9% of them had made diagnoses from oral manifestations, 51.3% (77) were not able to treat these patients, and 69.3% (104) would refer patients to specialized centres for treatment. Moreover, 119 (79.3%) considered that a dental hygienist was a valid collaborator for the treatment of oral cavity manifestations. Regarding prophylaxis, 16.7% (25) suggested fluoride prophylaxis and 21.3% (32) oral hygiene education. Only 1.3% indicated the use of bicarbonate to change salivary pH values, suggested conservative or prosthetic restorations, suggested the use of saliva substitutes, or the sealing of permanent teeth. Difficulties in clinically treating these patients were related to a lack of knowledge for 72% (108) of participants. Of them, 36.7% (55) had studied the clinical aspects of this pathology while attending dental school and 24.7% (37) after their degree. In total, 94.7% (142) expressed the need for further information and only 2% (3) considered they had sufficient clinical knowledge. Conclusions: It is evident that there is a lack of knowledge regarding the problem and there would seem to be an urgent need to provide more training programs and to establish guidelines for the diagnosis and treatment of eating disorders among dentists. In our opinion, the acquisition of such knowledge will change the approach to related pathology, improving clinical skills, and subsequently diagnosis and treatment.